Male genital titillators and the intensity of post-copulatory sexual selection across bushcrickets. (10th July 2017) - Lehmann, Gerlind U.C; Gilbert, James DJ; Vahed, Karim; Lehmann, Arne W
Lay Summary: We examined the relationships between the complexity of male genital structures (titillators) and both the mating rate of males and females, and the number of times females mate, across a range of bushcricket species. We did not find any relationship between genital complexity and the number of times females mate. Among species with titillators, however, the complexity of these structures was associated with faster re-mating rates in females. The results therefore only partly support the hypothesis that the structure and complexity of genitalia relate to the intensity of sexual selection. Abstract: Animal genitalia are diverse and a growing body of evidence suggests that they evolve rapidly under post-copulatory sexual selection. This process is predicted to be more intense in polyandrous species, although there have been very few comparative studies of the relationship between the complexity of genital structures in males and measures of the degree of polyandry. In some bushcricket families, males possess sclerotized copulatory structures known as titillators, which are inserted into the female's genital chamber and moved rhythmically. Like other genital structures, bushcricket titillators are widely used as important taxonomic characters and show considerable variation across species in structure, shape, and the extent to which they are spined. Here, we examine relationships between the presence/absence of titillators, titillator complexity, and both mating frequency and the degree of polyandry in bushcrickets, using phylogenetic comparative analyses. Using published sources combined with original observations, data were obtained for the mean level of polyandry, the duration of the male and female sexual refractory periods, and the level of complexity of titillators. To analyze data, we fitted phylogenetic generalized least squares models. No significant relationships were found between titillator presence or complexity and either the level of polyandry, duration of the male's sexual refractory period, or the ratio of the female and male sexual refractory periods. The duration of the female's refractory period, however, was positively associated with titillator presence and negatively associated with titillator complexity. The data therefore partially support the hypothesis that post-copulatory sexual selection drives genital evolution in this taxon.